Macroeconomic Variables, Global Stock, and Financial Sector Stock Indices in Indonesia - Aam Slamet Rusydiana; Dito Prakoso; Ihsanul Ikhwan (Management and Sustainability, 2022)
This study aims to analyze the impact of macroeconomic variables and global stock indices on the financial sector stock index in Indonesia. The data used is secondary data in the form of monthly time series from January 2010 to December 2019, which comes from Bank Indonesia, the Central Bureau of Statistics (BPS), and Yahoo Finance. The variables of this study include the Jakarta Islamic Index (Indonesia), IDX Sectoral Index (Indonesia), Money Supply Inflation, Rupiah against USD Exchange Rate, Crude Palm Oil Price, Industrial Production Index, KL Financial Sectoral Index (Malaysia), SET Financial Sectoral Index (Thailand) and S&P 500 Stock Index (USA). The analysis method used is Autoregressive Distributed Lag (ARDL). The results concluded that the short-term estimation resulted in the exchange rate variable, the Industrial Production Index (IPI), and the Thailand SET financial sector stock index having a significant effect on the JII index, while the money supply variable, the Malaysia KL financial sector stock index, the Thailand SET financial sector stock index, and the US S&P 500 stock index had a significant effect on the IDX financial sector index. Then, the long-term estimation found that the Thailand SET financial sector stock index variable has a significant effect on the JII. Then, in the IDX financial sector index model, there are two significant variables, namely money supply and Industrial Production Index.